2010
DOI: 10.3176/eco.2010.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vegetation performance on semicoke dumps of Kohtla-Järve oil shale industry, Estonia

Abstract: The performance of vegetation was assessed at semicoke dumping sites of Kohtla-Järve oil shale industry in summers 2004 and 2006. The condition of tree species and the presence of herbaceous species were recorded in areas where the vegetation had been planted or had developed naturally. Betula pendula and Populus balsamifera were the most abundant tree species on the semicoke dumps covering 0.54 and 0.11 km 2 , respectively. Herbaceous vegetation had the highest coverage in stands dominated by Alnus glutinosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Even if the overall vegetation composition of reclaimed sites resembles that of the surrounding forest, a number of forest species may still be missing due to colonisation and recruitment problems [30,31]. Studies of reclaimed Estonian oil shale and Czech coal mining sites have shown that different tree species have different impacts on the diversity and composition of understory [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the overall vegetation composition of reclaimed sites resembles that of the surrounding forest, a number of forest species may still be missing due to colonisation and recruitment problems [30,31]. Studies of reclaimed Estonian oil shale and Czech coal mining sites have shown that different tree species have different impacts on the diversity and composition of understory [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…We expect that a thorough revision of New Zealand specimens of early collectors and explorers, such as J. Everard Home, Allan and Richard Cunningham, which were recently revealed in the Turczaninow historical herbarium at KW, may bring important and interesting results not only on native plants (including type specimens), but also for non-native species introduced during the early stages of the European colonization, which will document their earliest stages of expansion. Питаннями колонізації вищими рослинами відвалів Криворізького залізорудного басейну займаються більше 50 років (Dobrovolskyi et al, 1979;Reva et al, 1993;Pavlenko et al, 2017). Серед піонерних видів, які успішно колонізують техногенно порушені ландшафти Криворіжжя, виділяється Betula pendula Roth, що оселяється та щорічно утворює самосів навіть на тих територіях, де ще відсутні квіткові трав'яні рослини (Korshikov, Krasnoshtan, 2012).…”
Section: Discussionunclassified
“…Протягом останніх 20-30 років відбувається процес поселення, закріплення та розселення B. pendula на різних промислових відвалах Донбасу і Придніпров'я шляхом заносу плодів виду з насаджень, які знаходяться поблизу цих новостворених ландшафтів (Korshikov et al, 2012). В інших промислових регіонах у межах природного та інтродукційного ареалу B. pendula є активним піонером на техногенно порушених територіях і характеризується швидкими темпами розвитку (Muzafarova, 2006;Vaht, 2010), що проявляється у відносно ранньому початку плодоношення при невеликій масі дерева (Evstigneev, Korotkov, 1992;Konysbaeva, Ormanbekova, 2013) На досліджених відвалах ПівнГЗК, ЦГЗК субстрат складається в основному з кам'янистих порід різної щільності, серед яких переважають залізисті кварцити, меншою мірою -сланці (рис. 2), на Петрівському зустрічаються й граніти та пісковики (Safonova, Reva, 2009).…”
Section: вступunclassified
“…Betula рendula успішно зростає на сланцевих відвалах в Естонії, де він відновлюється природним шляхом і є найбільш поширеним з деревних видів. При цьому, під стовбурами 20-річних дерев виникає гумусовий шар з листової підстилки до 2 см (Vaht et al, 2010). До несприятливих умов при наявності високого вмісту важких металів B. рendula може адаптуватись на організменному рівні завдяки перебудові в анатомічній структурі пагонів (Andráš et al, 2007).…”
Section: результати та обговоренняunclassified